Who should bear the burden of increasing fiscal pressure? An optimal income taxation perspective - Mehmet Ayaz; Lea Fricke; Clemens Fuest; Dominik Sachs (EconPol Forum, 2023)
Governments need to either cut other spending or raise more tax revenue to service the additional debt resulting from shocks like the Covid-19 pandemic. This paper considers the case when governments decide to raise additional revenue. A key policy issue is how the additional tax burden should and will be distributed between households with different incomes. Generally, tax systems are progressive, but should they become more or less progressive in response to the shock?. Generally, governments that maximize welfare in a society with given preferences for redistribution face a tradeoff between raising tax revenue and redistributing between households. If they need to raise more, there is less room for redistribution. To effectively raise additional tax revenues, governments should increase taxes and cut transfers for all taxpayers. Measured in euros, the additional burden on rich households is higher than that on poor households, but marginal and average tax rates rise more for households with lower incomes. Thus, optimal tax progressivity should decrease in response to growing fiscal pressure. The difference between the actual and the revenue-maximizing marginal tax rates is a key statistic for the size of the increase in marginal tax rates across the income distribution. We find that this difference is highest for low incomes.
Keywords: 330